IMPLEMENTATION OF INFAQ FUND MANAGEMENT ACCORDING TO LAW NUMBER 12 OF 2021 ON BAITUL MAL IN PIDIE DISTRICT OF INDONESIA - Sa’dan, Farida Ayu Saputri; Isra’ Hirdayadi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
Indonesia has a state foundation, namely Pancasila. Caring for others is manifested through giving zakat, donations and giving alms. Interestingly, in Baitul Mal, income from infaq funds is regulated in Pidie Regent Regulation Number 12 of 2021 concerning infaq funds being charged. So in this work the researcher wants to look further into the implementation of Infaq management in Baitul Mal, Pidie Regency, how the Pidie Regency Regent's Regulation Number 12 of 2021 is compatible with Aceh Qanun Number 3 of 2021 and Islamic views with these regulations. The research method that the author uses in this discussion is the descriptive analysis method, namely to present a systematic and accurate description of the facts of the object to be studied, namely the description that the author will make based on data obtained from interviews with one of Baitul Mal Pidie and from several document sources and also open books which also contain how infaq management should be implemented. After seeing how infaq is regulated in Islam, and how infaq is regulated in Pidie Regent Regulation Number 12 of 2021. There is a gap here, which is why in the Regent's Regulations a reference is given to the level of Infaq and Islam does not regulate it, so that deducting Infaq from the monthly salary is not recommended because it violates one of the pillars of Infaq, namely that there is no element of compulsion in it.